A novel composite of micelles and hydrogel for improving skin delivery of hydrocortisone and application in atopic dermatitis therapy. (June 2020) - Yuan, Liping; Pan, Meng; Lei, Minyi; Zhou, Xingli; Hu, Danrong; Liu, Qingya; Chen, Yu; Li, Wei; Qian, Zhiyong
Graphical abstract: Highlights: A novel composite of hydrocortisone-loaded micelles and hydrogel was prepared. The composite significantly promoted delivery of hydrocortisone though the skin. With low dose hydrocortisone, the composite exhibited improved therapeutic effects. The composite had reduced local skin irritation and adverse systemic effects. Abstract: Transdermal drug delivery is an attractive and potentially more effective method of localized and systemic treatment with minimal side effects and greater safety than current techniques. However, a limitation of drug delivery through the skin is the presence of the stratum corneum, which inhibits the development of clinical applications. Furthermore, in order to achieve better therapeutic outcomes, a number of traditional topically-applied preparations have high drug concentrations which can lead to skin irritation and formation of lesions. The use of safer and milder hydrocortisone (HC) cream for the treatment of moderate to severe atopic dermatitis (AD) is not considered due to its low potency and poor absorption through the skin, even at a dose of 1%. Therefore, in the present study, a composite of HC-loaded micelles and carbomer hydrogel was designed to enhance transdermal HC transport to improve topical therapy of AD. Franz diffusion cell experiments indicated that this composite significantly increased the skin permeation rate and cumulative quantity of HC transferred, which were greater than a 9-fold and 50-fold increase relative to HC cream, respectively. In addition, the composite system was demonstrated to rapidly and effectively ameliorate inflammatory symptoms on an AD-like mouse model and greatly reduce skin irritation and adverse systemic effects compared to HC cream. As described above, the novel HC formulation was a feasible strategy to provide safe and effective treatment in AD therapy.